Psychosocial support during pregnancy: perceptions and expectations among pregnant teenagers in Ahvaz, Iran-a qualitative content analysis - Setareh Yousefi; Simin Montazeri; Nahid Javadifar; Saeed Ghanbari (Reproductive Health)
Abstract Background Teenage pregnancy remains a major global concern, with profound effects on young mothers and their families. Understanding the specific needs and expectations of pregnant adolescents regarding psychosocial support is crucial for developing effective interventions. This study explores how pregnant adolescents perceive and what they expect from psychosocial support during pregnancy. Methods A qualitative study was conducted in Ahvaz, Iran, from 2023 to 2024. Participants were selected using purposive sampling to ensure maximum diversity and included pregnant adolescents, family members, and healthcare providers. Data were gathered through 30 semi-structured, in-depth interviews and analyzed using conventional qualitative content analysis with MAXQDA 2020 software. To enhance validity, member checking was employed, allowing participants to verify the accuracy of the interpretations. Reliability was ensured by applying a consistent coding framework across all interviews. Results The analysis revealed three major themes: Challenges and Burdens– Participants reported societal stigma, emotional instability, limited family support, autonomy conflicts, and health issues, highlighting a disconnect between societal expectations and their lived realities. Positive Experiences and Adaptations– Despite challenges, many adolescents described resilience, the joy of motherhood, emotional bonding, personal growth, and improved spousal relationships. These experiences underscore the importance of strengths-based psychosocial support. Support and Intervention Needs– Participants emphasized the need for tailored education, active family involvement, and culturally sensitive healthcare to provide holistic care for pregnant adolescents. Conclusions These findings highlight the urgent need for culturally tailored interventions that address the unique developmental and psychosocial needs of adolescent mothers. Effective strategies should include targeted education, accessible counseling, active family engagement, and specialized training for healthcare providers. Implementing a comprehensive, strengths-based support framework is essential to promote the well-being and resilience of this vulnerable population.